Macro news and bond yield spreads in the euro area - Guglielmo Maria Caporale; Fabio Spagnolo; Nicola Spagnolo (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
This paper analyses the effects of newspaper coverage of macro news on the spread between the yield on the 10-year German Bund and on sovereign bonds in eight countries belonging to the euro area (Belgium, France, Greece, Ireland, Italy, the Netherlands, Portugal and Spain) using daily data for the period 1999-2014. The econometric analysis is based on the estimation of a VAR-GARCH model. The results can be summarised as follows. Negative news have significant positive effects on yield spreads in all PIIGS countries but Italy before September 2008; markets respond more to negative news, and their reaction has increased during the recent financial crisis. News volatility has a significant impact on yield spread volatility, the effects being more pronounced in the case of negative news and bigger in the most recent crisis period, especially in the PIIGS countries. Further, the conditional correlations between yield spreads and negative news are significant and positive, and their increase in absolute value during the financial crisis (especially in the PIIGS countries) indicates a higher sensitivity of yield spreads to negative releases.
Keywords: C32; F36; G15; 330; News; Yield Spreads; Volatility Spillovers; VAR-GARCH model